Medical students review of formative OSCE scores, checklists, and videos improves with student-faculty debriefing meetings. Issue 1 (1st January 2017) - Bernard, Aaron W.; Ceccolini, Gabbriel; Feinn, Richard; Rockfeld, Jennifer; Rosenberg, Ilene; Thomas, Listy; Cassese, Todd
ABSTRACT: Background: Performance feedback is considered essential to clinical skills development. Formative objective structured clinical exams (F-OSCEs) often include immediate feedback by standardized patients. Students can also be provided access to performance metrics including scores, checklists, and video recordings after the F-OSCE to supplement this feedback. How often students choose to review this data and how review impacts future performance has not been documented. Objective: We suspect student review of F-OSCE performance data is variable. We hypothesize that students who review this data have better performance on subsequent F-OSCEs compared to those who do not. We also suspect that frequency of data review can be improved with faculty involvement in the form of student-faculty debriefing meetings. Design: Simulation recording software tracks and time stamps student review of performance data. We investigated a cohort of first- and second-year medical students from the 2015-16 academic year. Basic descriptive statistics were used to characterize frequency of data review and a linear mixed-model analysis was used to determine relationships between data review and future F-OSCE performance. Results: Students reviewed scores (64%), checklists (42%), and videos (28%) in decreasing frequency. Frequency of review of all metric and modalities improved when student-faculty debriefing meetings were conducted (p<.001). Among 92 first-year students, checklist review was associated with an improved performance on subsequent F-OSCEs (p = 0.038) by 1.07 percentage points on a scale of 0-100. Among 86 second year students, no review modality was associated with improved performance on subsequent F-OSCEs. Conclusion: Medical students review F-OSCE checklists and video recordings less than 50% of the time when not prompted. Student-faculty debriefing meetings increased student data reviews. First-year student's review of checklists on F-OSCEs was associated with increases in performance on subsequent F-OSCEs, however this outcome was not observed among second-year students.